Impact of Sleep Duration on Depression and Anxiety After Acute Ischemic Stroke - Liu, Fei; Yang, Yang; Wang, Shuo; Zhang, Xiao-Li; Wang, An-Xin; Liao, Xiao-Ling; Fang, Hong-Juan; Qu, Yue; Ma, Wei-Guo; Zhang, Ning; Wang, Chun-Xue; Wang, Yong-Jun (Frontiers in Neurology, 2021)
Background: Abnormal sleep duration predicts depression and anxiety. We seek to evaluate the impact of sleep duration before stroke on the occurrence of depression and anxiety at 3 months after acute ischemic stroke (AIS). Methods: Nationally representative samples from the Third China National Stroke Registry were used to examine cognition and sleep impairment after AIS (CNSR-III-ICONS). Based on baseline sleep duration before onset of stroke as measured by using the Pittsburgh Sleep Quality Index (PSQI), 1,446 patients were divided into four groups: >7, 6–7, 5–6, and <5 h of sleep. Patients were followed up with the General Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) for 3 months. Poststroke anxiety (PSA) was defined as GAD-7 of ≥5 and poststroke depression (PSD) as PHQ-9 of ≥5. The association of sleep duration with PSA and PSD was evaluated using multivariable logistic regression. Results: The incidences of PSA and PSD were 11.2 and 17.6% at 3 months, respectively. Compared to a sleep duration of >7 h, 5–6 h, and <5 h of sleep were identified as risk factors of PSA [odds ratio (OR), 1.95; 95% confidence interval (CI), 1.24–3.07; P < 0.01 and OR, 3.41; 95% CI, 1.94–6.04; P < 0.01) and PSD (OR, 1.47; 95% CI, 1.00–2.17; P = 0.04 and OR, 3.05; 95% CI, 1.85–5.02; P < 0.01), while 6–7 h of sleep was associated with neither PSA (OR, 1.09; 95% CI, 0.71–1.67; P = 0.68) nor PSD (OR, 0.92; 95% CI, 0.64–1.30; P = 0.64). In interaction analysis, the impact of sleep duration on PSA and PSD was not affected by gender (P = 0.68 and P = 0.29, respectively). Conclusions: Sleep duration of shorter than 6 h was predictive of anxiety and depression after ischemic stroke.